Endocannabinoid–Dopamine Interactions in Striatal Synaptic Plasticity - Mathur, Brian N.; Lovinger, David M. (Frontiers in Pharmacology, 2012)
The nigrostriatal dopaminergic system is implicated in action control and learning. A large body of work has focused on the contribution of this system to modulation of the corticostriatal synapse, the predominant synapse type in the striatum. Signaling through the D2 dopamine receptor is necessary for endocannabinoid-mediated depression of corticostriatal glutamate release. Here we review the known details of this mechanism and discuss newly discovered signaling pathways interacting with this system that ultimately exert dynamic control of cortical input to the striatum and striatal output. This topic is timely with respect to Parkinson’s disease given recent data indicating changes in the striatal endocannabinoid system in patients with this disorder.